Genetic diversity and population structure in Beninese pigeon pea [Cajanus cajan (L.) Huth] landraces collection revealed by SSR and genome wide SNP markers - ADOUKONOU-SAGBADJA, Hubert (My University, 2020)
Pigeon pea [Cajanus cajan (L.) Huth] is a valuable multipurpose crop locally used for household food security as well in traditional medicine in Benin. However, due to the neglected status of the crop, its genetic resources are not well evaluated and its agronomic potential remains undetermined. For breeding purpose, a total of 77 landraces from Benin and three breeding lines were simultaneously genotyped with 30 preselected SSRs and 794 GBS derived SNPs in order to estimate the genetic diversity and infer the population structure within the collection. Both marker types were found informative in polymorphism analysis revealing all high genetic variability. The 30 SSR markers led to a total of 209 alleles with an average of 6.97 alleles per locus, whereas only biallelic SNPs were extracted from GBS data according to specific filter criteria. The polymorphism information content value was 0.57 and 0.25 for SSR and SNP, respectively. The genetic diversity calculated as expected heterozygosity was higher for SSR (0.62) than for SNP (0.35). The inference of the genetic structure subdivided the entire collection into three major groups independent of the marker type. However, the resolving power in population structure analysis was higher for SNP than for SSR. AMOVA and PCoA analyses showed clearer population structure with SNP than SSR. The present study provides a clear insight on the genetic diversity in Beninese pigeon pea and represents the first report comparing the performance of SSR and SNP markers for population genetics analysis in cultivated pigeon pea. It provides useful information for further pigeon pea conservation and breeding in Benin.
Keywords: Benin Genetic diversity Pigeon pea; Population structure Single nucleotide; polymorphisms (SNP) Simple sequence repeat (SSR)